2013
DOI: 10.1371/journal.pone.0064602
|View full text |Cite
|
Sign up to set email alerts
|

Too Fat to Fit through the Door: First Evidence for Disturbed Body-Scaled Action in Anorexia Nervosa during Locomotion

Abstract: To date, research on the disturbed experience of body size in Anorexia Nervosa (AN) mainly focused on the conscious perceptual level (i.e. body image). Here we investigated whether these disturbances extend to body schema: an unconscious, action-related representation of the body. AN patients (n = 19) and healthy controls (HC; n = 20) were compared on body-scaled action. Participants walked through door-like openings varying in width while performing a diversion task. AN patients and HC differed in the largest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 35 publications
9
130
2
Order By: Relevance
“…As stated above, patients with eating disorders, particularly anorexia nervosa, are thought to have deficits in the way they experience their own body, specifically by overestimating their actual body size (Slade and Russell 1973; Keizer et al 2013). This body size overestimation may therefore also be apparent, albeit to a lesser extent, for those with higher eating-disorder psychopathology in the healthy population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated above, patients with eating disorders, particularly anorexia nervosa, are thought to have deficits in the way they experience their own body, specifically by overestimating their actual body size (Slade and Russell 1973; Keizer et al 2013). This body size overestimation may therefore also be apparent, albeit to a lesser extent, for those with higher eating-disorder psychopathology in the healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been suggested that those with eating disorders, particularly anorexia nervosa, have a deficit in body perception. Many studies have shown anorexia patients to overestimate their body size (Slade and Russell 1973; Smeets 1999; Keizer et al 2011, 2013), although this phenomenon is still disputed (Cornelissen et al 2013). However, we do know that experimental modulation of perceived body size has a direct effect on body satisfaction in healthy individuals (Preston and Ehrsson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Like all mental illnesses, eating disorders are in part illnesses of interpretation—of meaning-creation gone wrong. The distortions involved may range from low-level perceptual and motor discrimination17 to high-level conceptual configurations,18 and interpretive prompts like works of fiction may intervene at multiple levels. Eating disorders thus offer a lens through which to study the ways in which interpretive activity can change under conditions of psychopathology, while interpretation can be seen as one of the fundamental dimensions on which the condition of disordered eating—like all other mental health conditions—is manifested.…”
Section: Narrative Interpretation Mental Health and Eating Disordermentioning
confidence: 99%
“…Intriguingly, recent results have revealed that individuals with anorexia show evidence for overestimation of body size in implicit action-based tasks (Guardia et al, 2010(Guardia et al, , 2012Keizer et al, 2013). Critically, these studies are less susceptible than overt size estimates to the critique of implicitly reflecting attitudes towards the body, rather than distorted body representation per se (cf.…”
Section: Implications For Clinical Disorders Of Body Representationmentioning
confidence: 99%